Family Succession and the Importance of Succession Planning - Rosa, Cintia Vitoria Panucci (2023)
Family businesses have a significant presence in the economic life of our country, whether due to their share of GDP or the number of jobs they generate, however, most do not survive the transition to the second generation. Therefore, it is relevant to understand the main conflicts that hinder family succession, as well as the main solutions that help to overcome these bottlenecks. Through applied research, with a descriptive objective, classified as qualitative and with a bibliographical study technique, it is concluded that the objectives of the work were achieved and that the hypotheses were confirmed. It was observed that the long-term planning of the succession process is essential to prepare the successor, the family, the company and society, thus ensuring a smooth transition and the longevity of the company. It is still possible to observe that there is no universal model that is applied to all companies, as each company has its peculiarities.